2000
DOI: 10.5465/1556344
|View full text |Cite
|
Sign up to set email alerts
|

Marginal Mentoring: The Effects Of Type Of Mentor, Quality Of Relationship, And Program Design On Work And Career Attitudes

Abstract: Employing a national sample of 1,162 employees, we examined the relationship between joh and career attitudes and the presence of a mentor, the mentor's type (formal or informal), the quality ofthe mentoring relationship, and the perceived effectiveness and design of a formal mentoring program. Satisfaction with a mentoring relationship had a stronger impact on attitudes than the presence of a mentor, whether the relationship was formal or informal, or the design of a formal mentoring program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
470
3
12

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 338 publications
(509 citation statements)
references
References 26 publications
(23 reference statements)
24
470
3
12
Order By: Relevance
“…Our question regarding mentoring is similar to questions used in previous research to determine whether or not employees had mentoring relationships (e.g. Allen and Poteet, 1999;Ragins et al, 2000). Overall, 110 of the 220 respondents (50%) reported that they had a mentor.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our question regarding mentoring is similar to questions used in previous research to determine whether or not employees had mentoring relationships (e.g. Allen and Poteet, 1999;Ragins et al, 2000). Overall, 110 of the 220 respondents (50%) reported that they had a mentor.…”
Section: Methodsmentioning
confidence: 99%
“…More information about the nature of mentoring relationships would also be useful. For instance, the quality of the mentoring relationship from the perspective of the protégé (Ragins et al, 2000) may play an important role in buffering the effects of broken promises. While we would expect that high-quality mentoring relationships would reduce the negative fallout from PCB, low-quality or dysfunctional mentoring relationships may actually create scenarios where employees respond to PCB in a more negative manner.…”
Section: Future Research Directionsmentioning
confidence: 99%
“…Mentorship in engineering has not been well researched, with even less work done on the mentorship patterns of women engineers. However, the broader literature supports the notion that men tend to benefit more from establishing mentoring relations from both the career-related support and psychosocial standpoints than women (Ragins and Cotton, 1999;Ragins, Cotton, and Miller, 2000). Not surprisingly, in a male-dominated profession such as engineering, women's access to mentors, not to mention the positive impact that they may gain from them is expected to be limited.…”
Section: A Undergraduate Work Experience Mentorship and The Role Omentioning
confidence: 99%
“…Mentoring relationship has attracted significant attention from scholars for over three decades (Chao 1997;Kram 1983Kram , 1985Ragins and Cotton 1999;Ragins, Cotton, and Miller 2000;Ragins and Kram 2007;Waters 2004), particularly of those in established organizations. Although many different definitions of mentors exist in the literature, it is generally accepted that mentors in the existing organizations are senior employees who provide career guidance and personal advice to new employees (Haggard et al 2011).…”
Section: Mentorship Support: Importance Of Observing and Emulating Mementioning
confidence: 99%